Model Tradisi Adat “Tepung Tawar” Dalam Penyelesaian Konflik Pengelolaan Sumber Daya Alam - Junaidi, Junaidi (Zaaken: Journal of Civil and Business Law, 2024)
The numerous disputes over the exploitation of natural resources mark this condition. Conflict resolution without going through the judicial route by utilizing the customary system has been passed down through generations in the life of customary law communities in Indonesia. The way to resolve conflicts based on Indonesian customary traditions aligns with values of justice that are prioritized over legal certainty. Conflict resolution through a familial approach is called "tepung tawar" and is one type of local wisdom practiced by the community in South Sumatra. The research discusses how the "tepung tawar" model is used in resolving natural resource conflicts and the strengthening of "tepung tawar" in customary institutions as legislation. This research method uses normative legal research. Tepung tawar is a method of non-litigious conflict resolution through deliberation, where by discussing, both parties can reach an agreement that is mutually beneficial in a peaceful manner. Tepung tawar in customary law can serve as a foundation for resolving conflicts related to natural resource management. Serious efforts are needed to empower customary law by the government through its regulation in legislation.